The parathyroid hormone family of peptides: structure, tissue distribution, regulation, and potential functional roles in calcium and phosphate balance in fish - Guerreiro, P. M. (2014)
Parathyroid hormone (PTH) and PTH-related protein (PTHrP) are two factors that share amino acid sequence homology and act via a common receptor. In tetrapods, PTH is the main endocrine factor acting in bone and kidney to regulate calcium and phosphate. PTHrP is an essential paracrine developmental factor present in many tissues and is involved in the regulation of ossification, mammary gland development, muscle relaxation, and other functions. Fish apparently lack an equivalent of the parathyroid gland and were long thought to be devoid of PTH. Only in recent years has the existence of PTH-like peptides and their receptors in fish been firmly established. Two forms of PTH, two of PTHrP, and a protein with intermediate characteristics designated PTH-L are encoded by separate genes in teleost fish. Three receptors encoded by separate genes in fish mediate PTH/PTHrP actions, whereas only two receptors have so far been found in terrestrial vertebrates. PTHrP has been more intensively studied than PTH, from lampreys to advanced teleosts. It is expressed in many tissues and is present in high concentration in fish blood. Administration of this peptide alters calcium metabolism and has marked effects on associated gene expression and enzyme activity in vivo and in vitro. This review provides a comprehensive overview of the physiological roles, distribution, and molecular relationships of the piscine PTH-like peptides.